(3GdeMce hGdeJTGHg ef GdbQBf GdcQjes - (3CHh GdbGSe gHI Hf SdGeIs
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi Gddg JYGdi EHQGgje Hf eMeO MOKfi GdTjN GdEeGe Rjf GdeLGdS CHh GdbGSe Hf jhSa bGd GdMeO ddg GdPi gOGfG dOjfg , hLYdfG ef Cgdg s
(3BNQgG (B:s
(3BNQg eHJhQ , hBNQ GdehLhO efg ef GdBjI GdSGOSI ef ShQI GdfSGA bhdg (B: (3Ke JdG bhdg JYGdi Ke JehJhf ef bQjH aChdFc gh abGd GdfHi Udi Gddg Ydjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3ai GdfSGN hGdefShNs
(3cJHJ HYV GdYfhGfGJ HGdMeQI hHYVgG HGdShGO eLhOkGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3MOjK (B118) s
Keywords: (3GdMOjK h GdeUWdMs